1991
DOI: 10.1182/blood.v78.7.1697.1697
|View full text |Cite
|
Sign up to set email alerts
|

Infection of megakaryocytes by human immunodeficiency virus in seropositive patients with immune thrombocytopenic purpura

Abstract: Twenty-one human immunodeficiency virus (HIV)-positive patients, including 11 acquired immunodeficiency syndrome (AIDS)-free patients with immune thrombocytopenic purpura (ITP), were studied to determine whether the megakaryocytic/platelet lineage was infected by HIV. Because purification of platelets did not reach a level sufficient for unequivocal results by the polymerase chain reaction, in situ hybridization was thus performed. Purified marrow megakaryocytes (MK) from 10 HIV-infected ITP patients were stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0
2

Year Published

1996
1996
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(37 citation statements)
references
References 31 publications
2
33
0
2
Order By: Relevance
“…Another possible mechanism that may account for the occurrence of antiplatelet antibodies in HIV patients is the presence of specific HIV antigens on the platelet membrane due to an HIV infection of the megakaryocyte/platelet lineage. In support of this hypothesis, it has been reported that human megakaryocytes have a functional CD4 molecule capable of binding HIV (Kouri et al, 1993), and that megakaryocytes from HIV-infected thrombocytopenic patients express HIV transcripts or proteins (Zucker-Franklin & Cao, 1989;Louache et al, 1991). However, whether human megakaryocytes are truly infected by HIV, i.e.…”
Section: Discussionmentioning
confidence: 98%
“…Another possible mechanism that may account for the occurrence of antiplatelet antibodies in HIV patients is the presence of specific HIV antigens on the platelet membrane due to an HIV infection of the megakaryocyte/platelet lineage. In support of this hypothesis, it has been reported that human megakaryocytes have a functional CD4 molecule capable of binding HIV (Kouri et al, 1993), and that megakaryocytes from HIV-infected thrombocytopenic patients express HIV transcripts or proteins (Zucker-Franklin & Cao, 1989;Louache et al, 1991). However, whether human megakaryocytes are truly infected by HIV, i.e.…”
Section: Discussionmentioning
confidence: 98%
“…Thrombooiesisand/or megakaryocytopoiesis could be impaired either by direct infection of CD4 MK progenitors or by an indirect mechanism involving altered cytokine production by an infected accessory cell. A variety of evidence has been offered to suggest that cells of the MK lineage can be infected by HIV-1 (Zucker-Franklin et al, 1989;Kouri et al, 1993;Sakaguchi et al, 1991;Louache et al, 1991;Zucker-Franklin & Cao, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…This decreased production of platelets may be caused by bone marrow infiltration of opportunistic infection or malignancy, or by HIV-1 infection of platelet precursors. HIV-1 can infect megakaryocytes in vitro and has been detected in megakaryocytes isolated from patients with HIV-1 TP (25,95,106,162). Because megakaryocytes and their precursors express CD4 and CXCR4, but not CCR5, there should be a preponderance of CXCR4-tropic HIV-1 (X4 HIV-1) or dual tropic HIV-1 (R5X4 HIV-1) in the bone marrow of patients with HIV-1 TP (24).…”
Section: Chemokine Receptors and Hiv-1 Interactions With Platelets Anmentioning
confidence: 99%